Acute and Chronic Kernicterus: MR Imaging Evolution of Globus Pallidus Signal Change during Childhood - Gburek-Augustat, J.; Sorge, I.; Stange, M.; Kern, J.; Merkenschlager, A.; Nägele, T.; Krägeloh-Mann, I. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Despite its rarity in Western countries, kernicterus resulting from severe neonatal hyperbilirubinemia and its associated neurologic consequences still persists. Subtle MR imaging patterns may be overlooked, leading to diagnostic and prognostic uncertainties. The study systematically analyzes MR imaging pattern over time.MATERIALS AND METHODS: A retrospective MR imaging study was conducted in Departments of Pediatric Neurology at the University Children's Hospitals in Leipzig, Germany, or Tübingen, Germany, between 2012 and 2022 in patients who presented beyond the neonatal period suspected of having chronic kernicterus.RESULTS: Eight patients with a total of 15 MR images were identified. The clinical diagnosis of kernicterus was confirmed in all cases on the basis of typical MR imaging findings: Bilateral, diffuse hyperintensity of the globus pallidus was observed in the neonatal period on T1WI (1 MR imaging, at 2 weeks), in infancy on T2WI (4 MR images, at 9–26 months). In children 2 years of age and older, bilateral hyperintensity on T2WI was limited to the borders of the globus pallidus (8 MR images, at 20 months –13 years). Notably, 2 children exhibited normal initial MR imaging findings at 2 months of age. Hence, MR imaging depiction of kernicterus pathology evolves with time, first evident on T1WI, subsequently on T2WI, with a “blind window” during early infancy. The T2WI signal change initially involves the entire globus pallidus and later is limited to the borders. Kernicterus had not been diagnosed in any except 2 patients by previous investigators.CONCLUSIONS: All patients presented with a characteristic clinical history and signs and an evolving MR imaging pattern. Nonetheless, the diagnosis of kernicterus was frequently missed. Abnormalities on later MR images appear to be underrecognized.ABEacute bilirubin encephalopathyBFMFBimanual Fine Motor FunctionCPcerebral palsyGMFCSGross Motor Function Classification SystemGPglobus pallidus